2020
DOI: 10.1029/2019ja027013
|View full text |Cite
|
Sign up to set email alerts
|

Dynamically Unstable Strong Wind Shears Observed in the Polar Mesosphere Summer Echo Layer Associated With Geomagnetic Disturbances

Abstract: We report observations of dynamically unstable strong wind shear (Richardson number < 0.25) capable of inducing Kelvin‐Helmholtz instability in the polar mesospheric summer echoes (PMSE) layer (80–90 km) using very high frequency radar measurements in Kiruna (67.8°N, 20.4°E), Sweden, in 2006. The unstable strong wind shear can play an important role in producing PMSE by inducing turbulence and adiabatic cooling. We find that the strong shears take up 64% of the observed wind profiles and are frequently compose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…The recurrent geomagnetic storms are believed to be triggered by periodic oscillations in solar winds (Lei et al., 2008; Tsurutani et al., 2006; Temmer et al., 2007). Energetic particle precipitations during recurrent geomagnetic activities can modulate the temperature and ozone in the MLT region, which leads to disturbances in mesospheric neutral densities and neutral winds in the polar region (Lee et al., 2020; Meredith et al., 2011; Yi, Reid, Xue, Younger, Murphy, et al., 2017). Using the temperature and ozone measured by the Sounding of the Atmosphere using Broadband Emission Radiometry (SABER) instrument on the Thermosphere Ionosphere Mesosphere Energetics Dynamics (TIMED) satellite (version 2.0 level 2A), we further examine the MLT temperature and ozone evolutions over BJ during the recurrent geomagnetic storms in the autumn of 2018.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The recurrent geomagnetic storms are believed to be triggered by periodic oscillations in solar winds (Lei et al., 2008; Tsurutani et al., 2006; Temmer et al., 2007). Energetic particle precipitations during recurrent geomagnetic activities can modulate the temperature and ozone in the MLT region, which leads to disturbances in mesospheric neutral densities and neutral winds in the polar region (Lee et al., 2020; Meredith et al., 2011; Yi, Reid, Xue, Younger, Murphy, et al., 2017). Using the temperature and ozone measured by the Sounding of the Atmosphere using Broadband Emission Radiometry (SABER) instrument on the Thermosphere Ionosphere Mesosphere Energetics Dynamics (TIMED) satellite (version 2.0 level 2A), we further examine the MLT temperature and ozone evolutions over BJ during the recurrent geomagnetic storms in the autumn of 2018.…”
Section: Discussionmentioning
confidence: 99%
“…(2015) found evidence of neutral temperature enhancements in the MLT region during geomagnetic storms, which is caused by the southward transport of the storm‐time heating zone. Anomalies of neutral winds in the MLT region have been also found during geomagnetic storms (e.g., Lee et al., 2020; Salah & Goncharenko, 2001). Using the Thermosphere Ionosphere Mesosphere Electrodynamics General Circulation Model simulations at mid‐latitudes, Li et al.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…The shear persisted for more than 6 min. Lee et al (2020) investigated using a hodogram to determine whether the shear is connected to winds propagating from lower altitudes. The findings revealed that the shear was independent of the upward propagation of wind and instead abruptly occurred at local altitudes.…”
Section: Zonal Velocity and Echo Intensity Profilesmentioning
confidence: 99%
“…Recently, energetic electron precipitation induced by geomagnetic disturbance has been recognized as a significant contributor to PMSE production (Zeller & Bremer 2009;Kirkwood et al 2013;Lee et al 2013Lee et al , 2014Lee et al , 2015Lee et al , 2018Lee et al , 2020. During high-speed solar wind streams (HSSs), PMSE exhibits periodicities of 7, 9, and 13.5 days, in phase with solar wind speed and the auroral electrojet (AE) index (Lee et al 2013).…”
Section: Introductionmentioning
confidence: 99%